Historiography and International Relations (Czech Journal of International Relations, 1967)
In the ongoing discussion, the need for scientific research in international relations was generally stated. It is necessary to realize that it is mainly a proclamation the needs of scientific research of international relations, from the need to predict the results and the possibilities of this research so far, which has enlightened some questions certainly remarkable results, which, however, are very early and this applies especially to some areas of the world.The necessity of scientific research on development international influence after the Second World War, so strongly felt today by practical politics, however, also raised a number of new questions. Doubts were mainly expressed about the possibilities of the relationship between scientific disciplines, and in connection with that, the opinion that a new scientific discipline should be chosen, which would become a tool for scientific knowledge of the complex phenomena of contemporary international development. This opinion was generally accepted in the ongoing discussion.